Two new species of the ant spider genus Asceua Thorell, 1887 (Araneae: Zodariidae) from China - Zhang, Bao-Shi; Zhang, Feng; Jia, Xiao-Mei (Zootaxa, 2012)
Two new spider species of the genus Asceua are reported from China, Asceua quadrimaculata sp. nov. (male, female) and A.anding sp. nov. (female). A. torquata (Simon, 1909) is newly recorded from China, and its male is described and illustrated for the first time.